Unattended grieving in the context of COVID 19 in Botswana: Psycho-pastoral accompaniment - Madigele, Tshenolo; Tshelametse, Ronald (Stellenbosch Theological Journal, 2024)
This article explores the phenomenon of unattended grieving in the context of the COVID-19 pandemic in Botswana. It focuses on the integration of psychological and pastoral care approaches to provide psycho-pastoral accompaniment for individuals experiencing grief during this crisis. The article examines the unique challenges faced by individuals in processing their grief and proposes a comprehensive approach that combines psychological interventions with pastoral support. It is believed that by adopting the psycho-pastoral accompaniment approach, individuals in Botswana can effectively navigate the grieving process and find solace and healing beyond the pandemic.